Comparative Study on Ph Change in Root Dentine & Gutta Percha - Amit Bajirao Jadhav (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Ca(OH)2 produces a pH of over 11.1 which contributes to its antibacterial effects. Necrotic pulp and dentin has a pH of 6.0–7.4, however, after placing Ca(OH)2 in the canal, the peripheral dentin has a pH range of 7.4–9.5. Aim: To evaluate change of pH in root dentine (RD) & GP. Material & method: 120 sample single extracted tooth assessed for pH with 2 different groups i.e group 1 as Ca(OH)2 with vehicle for RD and grouup 2 with MGP. Result: We found statistically significant change for RD & GP. Conclusion: We come to conclude that , an alkaline pH was present in Ca(OH)2 preparation & MGP.